A study of the development of sectional titles in South Africa since the promulgation of the Act in 1971 - Coetzee, K R (Department of Civil Engineering, 2020)
During the l?st few years, much has been said in the local newspapers about Sectional Titles and most of what has been said was enough to scare most people from buying homes under Sectional Title. Admittedly Sectional Titles is a new innovation to the property market of South Africa because it is different from the normal situation whereby a person can now buy a section of a building whereas previously a person could only buy a plot of ground with or without a building on it. In other words, the block of flats of which each unit could only be rented, or in some cases in recent years, be "bought" on Blockshare basis (which will be discussed later), can now be individually bought as well as the owner now having a pro rata share in common property which consists of, inter alia, the passages, the roof, the grounds on which the building is situated, the swimming pool etc.